Assessing subsoil void hazards along a road system using H/V measurements, ERTs and IPTs to support local decision makers. Issue 3 (1st April 2018) - Pazzi, Veronica; Ceccatelli, Mattia; Gracchi, Teresa; Benedetta Masi, Elena; Fanti, Riccardo
ABSTRACT: Between 2008 and 2014, nine sinkholes occurred in northeastern Elba Island (Tuscany, Italy), an area with mostly flat terrain (called "Il Piano") separating the municipalities of Rio nell'Elba and Rio Marina. The last sinkhole damaged the only road (SP26) between the harbour of Rio Marina and the northwestern part of the island. A bypass was immediately built, but the SP26 remains closed. Considering that sinkholes could be densely clustered in sinkhole prone areas, their detection and forecasting are key aspects of local administrative policies. In this paper, we present the results of an integrated geophysical survey aimed at (i) characterizing the geology of the area surrounding the SP26, and (ii) assessing the subsoil void hazard around the road system to support the decision to replace or restore the SP26. Therefore, for the purposes of this research, 120 singlestation seismic noise measurements were taken following the horizontal‐to‐vertical spectral ratio (H/V) or Nakamura technique, while eight 2D electrical resistivity tomography (ERT) and 17 3D‐ERT/induced polarisation measurements were also carried out in the study area. The H/V method allowed the estimation of the mean thickness of the alluvium, whereas the 2D/3D‐ERTs and IPTs permitted the characterisation of the electrical behaviours of the materials and the localisation of the lenticular sand and gravel bodies within a sandy silt layer. The large amount of collected data made the zonation of the subsoil void hazards possible.